Pricing Power in Advertising Markets: Theory and Evidence - Gentzkow, Matthew; Shapiro, Jesse M.; Yang, Frank; Yurukoglu, Ali (American Economic Review, 2024)
Existing theories of media competition imply that advertisers will pay a lower price in equilibrium to reach consumers who multi-home across competing outlets. We generalize and extend this theoretical result and test it using data from television and social media advertising. We find that the model is a good match, qualitatively and quantitatively, to variation in advertising prices across demographic groups, outlets, platforms, and over time. We use the model to quantify the effects of competition within and across platforms. (JEL G34, K21, L13, L82, M37)